Linear chalaziosis. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2005)
Chalazion is a subacute or chronic inflammation of meibomian glands. The latter are sebaceous glands located in the fibrous part or tarsus of the conjunctiva, whose ducts open on the eyelid margin. On the other hand, stye is an acute inflammation of Zeiss glands. The latter are sebaceous glands surrounding the eyelashes, whose ducts open in the ciliary follicle near the eyelid margin. Stye and blepharitis can precede or be associated with chalazion. Simultaneous or subsequent occurrence of multiple chalazia is called chalaziosis. In the reported case the linear shape was likely due to the simultaneous inflammation of multiple meibomian glands. The pathogenesis of chalaziosis is not clarified, but probably affected by multiple factors as constitutional atopic and seborrheic factors, immunological factors (3), infectious factors mainly related to Staphylococcus aureus and dysmetabolic factors such as diabetes.